Brief historical overview of gamete donation related to Catholic sexual morality and the French bioethics law - Penna, Tullia (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The Catholic Church’s Magisterium deems as devoid of moral lawfulness gamete and embryo donation. The history of In vitro fertilization (IVF) pioneers perfectly shows how Catholic moral prohibitions have worked, as well as the origins of the French bioethical system. This system interpreted the medical and social practice of gamete donation through the lens of the concept of “don de couple à couple”, trying to address moral prohibitions. Nevertheless, in 2020 the bioethics law reform might change, fundamentally, this system. Parole chiave: Gamete, Donation; French Bioethics Law; Catholic Sexual Morality; IVF Indice: 1. Introduzione – 2. Cenni storici sulla procreazione medicalmente assistita – 3. L’integrazione della morale sessuale cattolica nel modello francese ideato da Georges David – 4. Conclusioni